MALAKA OSHIRISH TIZIMI MASHG’ULOTLARIDA SUN’IY INTELEKT TEXNOLOGIYALARIDAN FOYDALANISH TRANSFORMATSIYASI (CONFERENCE ON THE ROLE AND IMPORTANCE OF SCIENCE IN THE MODERN WORLD, 2025)
This scientific article presents a methodology for training competitive personnel by fostering students' creative thinking during classes through the use of artificial intelligence technologies. Additionally, it provides information on the possibilities of using artificial intelligence to transform the educational process from traditional to creative.